Quantitative Land Suitability Mapping for Crop Cultivation - Kokhan, Svitlana; Moskalenko, Antonina; Drozdivskyi, Oleg (Communications - Scientific Letters of the University of Zilina, 2018)
Developing the structure of geodatabase and knowledge base to provide quantitative mapping of land suitability for cultivation the main crops has been shown in the research. The general model and catalogs of knowledge base were designed that are structuring and formalizing information for creating thematic and complex maps and geomodels.The real world spatial problems give rise to multi-criteria decision-making based on geographical information systems (GIS). The GIS environment provides both aggregation and spatial analysis of various georeferenced data. In this paper, the two approaches of multi-criteria evaluation (MCE) are represented - overlaying with the AND operation and the lowest score assignment on one criterion. An example of multi-attribute decision analysis is done using criteria for the crop suitability assessment. A comparison of those two approaches has been made, based on results of the land-use suitability mapping for the study crops - winter wheat, sunflower and corn. The results demonstrated that at certain locations, a range of criteria values, according to the AND operations had the lower applicability and less flexibility than according to the second approach, based on the lowest score assignment on one criterion. Designed maps characterize the threshold status of the soil quality to provide yields of studied crops on certain areas.A set of land suitability maps, designed as quantitative models of integration of environmental, soil and climatic conditions, would be very effective to manage the complex decisions under the crop cultivation.
Keywords: knowledge base; geodatabase; land suitability; geoinformation mapping